The Influence of Stress on Pandemic Students - Stefanescu, Cristina (New Trends in Psychology, 2022)
In relation to the faculty, the student shows non-specific responses to the solicitations given by the faculty, specifically in the pandemic, when he had to adapt more to a new system, the online one. In the context of the crisis caused by the COVID-19 pandemic, the digital transformation of education has necessitated a rapid response, including from the European institutions. The digitalization of education provided the premises for the use of games for educational purposes, which can stimulate students' participation in the instructional-educational process. It matters a lot how we respond cognitively to stress, how we manage to interpret reality so that it is to our benefit. I'd rather see the full side of the glass and enjoy online interactions than be afraid that I might get infected if I went to college physically. Importantly, it is not the traumatic event itself that leads to growth (no one is grateful for COVID-19), but rather the way the event is processed.